When Should The Network Be The Computer? - Ports, Dan R. K.; Nelson, Jacob (17th Workshop on Hot Topics in Operating Systems (HotOS), 2019)
Researchers have repurposed programmable network devices to place small amounts of application computation in the network, sometimes yielding orders-of-magnitude performance gains. At the same time, effectively using these devices requires careful use of limited resources and managing deployment challenges. This paper provides a framework for principled use of in-network processing. We provide a set of guidelines for building robust and deployable in-network primitives, along with a taxonomy to help identify which applications can benefit from in-network processing and what types of devices they should use.